NCOA4-RET and TRIM27-RET Are Characteristic Gene Fusions in Salivary Intraductal Carcinoma, Including Invasive and Metastatic Tumors: Is "Intraductal" Correct? - Skálová, Alena; Ptáková, Nikola; Santana, Thalita; Agaimy, Abbas; Ihrler, Stephan; Uro-Coste, Emmanuelle; Thompson, Lester D R; Bishop, Justin A; Baněčkova, Martina; Rupp, Niels J; Morbini, Patrizia; de Sanctis, Stefano; et al. (The American journal of surgical pathology, 2019)
Intraductal carcinoma (IC) is the new WHO designation for tumors previously encompassed by "low-grade cribriform cystadenocarcinoma" and "low-grade salivary duct carcinoma." The relationship of IC to salivary duct carcinoma (SDC) is controversial, even though they are considered to be distinct entities. IC is a rare low-grade malignant salivary gland neoplasm with histopathological features reminiscent of atypical ductal hyperplasia or ductal carcinoma in situ of the breast, showing diffuse S100 protein and mammaglobin positivity, while it is partially defined genetically. Recently, RET rearrangements including NCOA4-RET and TRIM27-RET have been described in IC. Here, we genetically characterize the largest cohort of IC to date (33 cases) including 8 cases with focal or widespread invasive growth and 1 case with lymph node metastasis. Thirty-three cases of IC were analyzed by next-generation sequencing (NGS) using the FusionPlex Solid Tumor kit (ArcherDX). Identified gene fusions were confirmed using fluorescence in situ hybridization break-apart and fusion probes and an reverse transcription polymerase chain reaction designed specifically for the detected breakpoints. Ten cases of SDC were analyzed for comparison using NGS panels that detect mutations and fusion transcripts. NGS analysis detected an NCOA4-RET fusion transcript in 11 cases of intercalated duct-type IC joining exon 7 or 8 of NCOA4 gene and exon 12 of the RET gene. Eight cases of IC had an invasive growth pattern, including one with widespread invasion and lymph node metastasis. Three invasive ICs harbored an NCOA4-RET fusion transcript, while 1 case was negative, and 2 cases were not analyzable. In addition, a novel TRIM27-RET fusion transcript between exon 3 of TRIM27 and exon 12 of RET was identified in 2 cases of IC with apocrine features, and one of them displayed invasive growth. Two IC cases with invasive growth harbored novel fusions TUT1-ETV5 and KIAA1217-RET, respectively. A total of 42.4% of the cases in this series of IC harbored fusions involving RET. Such fusion transcripts were not detected in any of the 10 SDC cases. We have confirmed NCOA4-RET as a predominant fusion in intercalated duct-type IC, including 3 cases with invasive growth pattern. A novel finding in our series was a case of widely invasive intercalated duct-type IC, with a single lymph node metastasis that revealed an NCOA4-RET fusion transcript. We also demonstrated that a subset of apocrine ICs harbored a TRIM27-RET gene fusion, including one case with invasive growth. In contrast, neither NCOA4-RET nor TRIM27-RET fusions were detected in any tested SDCs. Thus, the distinct molecular findings in IC and SDC support that the tumors are separate malignant salivary tumor entities. The presence of tumor-type-specific NCOA4-RET or TRIM27-RET translocations in a subset of widely invasive carcinomas with intercalated duct-like immunoprofiles suggests that a recharacterization of IC including its redesignation as "intercalated duct carcinoma, invasive or noninvasive" may be appropriate.
Keywords: senioři; Genetic Predisposition to Disease; Neoplasm Invasiveness; jaderné proteiny; DNA-Binding Proteins; nádory slinných žláz; senioři nad 80 let; hybridizace in situ fluorescenční; Nuclear Proteins; Terminology as Topic; mladiství; terminologie jako téma; Carcinoma, Intraductal, Noninfiltrating; lymfatické metastázy; Middle Aged; mužské pohlaví; Adult; In Situ Hybridization, Fluorescence; Gene Fusion; Biomarkers, Tumor; polymerázová řetězová reakce s reverzní transkripcí; protoonkogenní proteiny c-ret; Lymphatic Metastasis; Aged, 80 and over; Nuclear Receptor Coactivators; intraduktální neinfiltrující karcinom; ženské pohlaví; nádorové biomarkery; Humans; koaktivátory jaderných receptorů; Proto-Oncogene Proteins c-ret; High-Throughput Nucleotide Sequencing; invazivní růst nádoru; lidé středního věku; Salivary Gland Neoplasms; vysoce účinné nukleotidové sekvenování; fúze genů; DNA vazebné proteiny; Reverse Transcriptase Polymerase Chain Reaction; dospělí; genetická predispozice k nemoci; Female; Aged; Adolescent; lidé; Male